2014
DOI: 10.1002/nbm.3118
|View full text |Cite
|
Sign up to set email alerts
|

Prostate MR elastography with transperineal electromagnetic actuation and a fast fractionally encoded steady‐state gradient echo sequence

Abstract: Our aim is to develop a clinically viable, fast-acquisition, prostate MR elastography (MRE) system with transperineal excitation. We developed a new actively shielded electromagnetic transducer, designed to enable quick deployment and positioning within the scanner. The shielding of the transducer was optimized using simulations. We also employed a new rapid pulse sequence that encodes the three-dimensional displacement field in the prostate gland using a fractionally encoded steady-state gradient echo sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 21 publications
0
35
0
Order By: Relevance
“…In this work PZ was found to be stiffer than CG; agreeing with earlier observations (Krouskop et al , 1998; Kemper et al , 2004) (mechanical frequencies: 0.1–4.0 Hz, and 65 Hz respectively). However some in vivo work has reported higher elastic modulus values in the CG compared with the PZ for healthy volunteers (Sahebjavaher et al , 2014) (70 Hz mechanical wave frequency). However (Sahebjavaher et al , 2014) also reported data for a prostate cancer patient for whom E was higher in the PZ compared with the CG.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In this work PZ was found to be stiffer than CG; agreeing with earlier observations (Krouskop et al , 1998; Kemper et al , 2004) (mechanical frequencies: 0.1–4.0 Hz, and 65 Hz respectively). However some in vivo work has reported higher elastic modulus values in the CG compared with the PZ for healthy volunteers (Sahebjavaher et al , 2014) (70 Hz mechanical wave frequency). However (Sahebjavaher et al , 2014) also reported data for a prostate cancer patient for whom E was higher in the PZ compared with the CG.…”
Section: Discussionmentioning
confidence: 97%
“…However some in vivo work has reported higher elastic modulus values in the CG compared with the PZ for healthy volunteers (Sahebjavaher et al , 2014) (70 Hz mechanical wave frequency). However (Sahebjavaher et al , 2014) also reported data for a prostate cancer patient for whom E was higher in the PZ compared with the CG. (Dresner et al , 1999) used dynamic MRE (mechanical frequency 100–600 Hz) on ex vivo prostate specimens, and found that for non-cancerous prostate the CG was stiffer than PZ, while cancer increased stiffness in the PZ, and also demonstrated that prostate shear modulus increases with the mechanical driving frequency, and therefore prostate tissue exhibits viscoelastic properties.…”
Section: Discussionmentioning
confidence: 97%
“…Recently, MR elastography has also proved capable of providing an elasticity image of the prostate. Although MR imaging shows promise, only a few clinical studies have been performed yet, and these were performed in a limited number of patients (38,39).…”
Section: Implications For Patient Carementioning
confidence: 98%
“…A shielded electromagnetic transducer was placed against the perineum of the subject in the supine position (13,14), as shown in Fig. 1.…”
Section: Setup and Acquisitionmentioning
confidence: 99%